Greek apologists of the second century - Grant, Robert M. 1917-2014 (Westminster Press, 1988)
Apologetic literature emerges from minority groups seeking to come to terms with the larger cultures within which they live. Its authors are not entirely at home in either their own groups or the larger society, and therefore their position is one with which many Christians today can sympathize. Professor Grant's new book looks at the first Christian apologists of all and the background to their message. After opening chapters discussing early Christian apologetic and its historical setting in the Roman empire, he looks in detail at Justin, Apollinaris of Hierapolis, Melito of Sardis, Athenagoras of Athens, Tatian, Theophilus of Antioch and other related figures including Celsus, Marcus Aurelius and the Gallican martyrs. He ends by tracing apologetic through the third century and into the Middle Ages. Apologetic can be attractive to readers today, but the main theme of the book is that while there is a certain timeless character to the Christian apologists of the second century, they are deeply involved in the political and social struggles of their time and cannot be understood apart from the precise circumstances in which they are writing.